PERBEDAAN PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA DITINJAU MELALUI APLIKASI PENDEKATAN PEMBELAJARAN SAVI BERBASIS LINGKUNGAN DAN PEMBELAJARAN EKSPOSITORI - Muhammad Daut Siagian; Metrlitna Br Sembiring (Universitas Islam Sumatera Utara, 2018)
Abstract. The purpose of this study was to analyze and describe students' mathematical connection abilities reviewed through the application of SAVI learning approach based on environment and expository learning. This research is a quasi-experimental research, in this study consists of three stages, namely the preparation stage, the implementation phase and the data analysis phase. This study took two parallel classes which were randomly homogeneous by applying different learning methods, namely the experimental and control classes. Based on the results of data processing obtained Fcount for learning is 119,653 with a significance of 0,000 0,05. Then H0 is rejected or Ha is accepted. This means that there are differences in the increase in mathematical connection skills between experimental class students and control class students. Besides that, it can also be concluded that the increase in students' mathematical connection skills through the application of the SAVI learning approach based on environment is higher than the students whose learning uses expository learning.Keywords: Mathematical Connection, SAVI, Environment Based, Expository.